ANALYSIS OF THE APPLICATION OF CASH DISBURSEMENT SYSTEMS AND PROCEDURES USING INVENTORY MONEY (UP) AT THE NAGAN RAYA SOCIAL SERVICE - Aflina, Cut Muti (Transpublika Publisher, 2022)
Changes in the government system from a system-centered system to regional autonomy which has a major effect on the implementation of government administration and also the scope of performance. This also has an effect on regulations on the financial system of local government. Cash disbursement is one of the most important resource components for achieving good governance. Cash disbursements have procedures which must comply with applicable rules. This expenditure system is inventory money provided in filling out each SKPD which is carried out only once a year. This research seeks to find out how to disburse inventory money cash in the Social Service of Nagan Raya Regency. The research method in which the researcher uses descriptive qualitative methods. The findings revealed that the cash disbursement system and procedure for the Nagan Raya Regency Social Service which has followed the Nagan Raya Regent Regulation No. 900/2/Kpts/2019 concerning the determination of the amount of the letter of request for payment of inventory money (SPP-UP) and the letter of request for payment of money change (SPP-GU) in Nagan Raya district government. It is expected that for the leadership of the Nagan Raya Regency Social Service to increase and maintain cash disbursement systems and procedures by conducting socialization of policies and authorities in improving the technical quality of existing human resources so that there is a positive effect on the cash disbursement system in the inventory money.